Experience of adults with cystic fibrosis: a perspective based on social phenomenology - Samara Macedo Cordeiro; Maria Cristina Pinto de Jesus; Renata Evangelista Tavares; Deise Moura de Oliveira; Miriam Aparecida Barbosa Merighi
ABSTRACT Objective: To understand the experience of adults living with cystic fibrosis. Method: A qualitative study based on the social phenomenology by Alfred Schütz, carried out with 12 adults interviewed in 2016. The statements were analyzed and organized into concrete categories. Results: The following categories were evidenced: "The biopsychosocial impact of the disease on daily life", "Social prejudice as a generator of embarrassment", "Coping strategies" and "Fear, uncertainties and the desire to carry out life projects". Final considerations: The understanding of the experience lived by adults with cystic fibrosis allowed unveiling intersubjective aspects experienced by this public that should be considered by health professionals in the care of this group. It is up to the professionals involved in assisting these people to develop care strategies aimed at completeness, respect for the world of meanings of each individual, their life history, and intersubjectivity that is specially built in the relationship between professionals and people with cystic fibrosis.